Pengaruh Kompetensi, Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Sumber Daya Manusia - Airyq, Irnin Miladdyan; Hubeis, Aida Vitayala Sjafri; Sukmawati, Anggraini (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The era of globalization presents several challenges related to human resource management. Every organization is appropriate to have qualified and highly competitive human resources to compete during dynamic changes. Employees as individuals and groups in an organization certainly have unique differences in personality. Employee performance can acquire optimal if they are experts in their fields and are established with a valuable organizational culture. Therefore, its purpose is to analyze the influence of competence, leadership, and organization culture on human resource performance and identify individual characteristics and factors that support employees. This research's location was at a non-profit organization, Ittihadul Islamiyah Welfare Charity Foundation (Ya BAKII), Cilacap district. The research data was obtained through filling out online questionnaires by 38 employees. Then it processed using Smart PLS tools for structural equation modelling (SEM) analysis. The results of the SEM-PLS test analysis prove that competence has a significant positive effect on performance, with the dominant indicator being professional competence. Organizational culture has a positive and well built relationship with improving employee performance, with innovation as the most authoritative indicator. Leadership can influence organizational culture positively and firmly as leadership has no significant effect on employee performance. Professional competence is the dominant sub-variable from the influence of competence on HR performance. While the leadership process in organizational culture can be developed through the application of relationship orientation by controlling employees. Organizational culture on HR performance can be improved through the application of innovation. Keywords: competence, organizational culture, leadership, SEM analysis